2009
DOI: 10.2108/zsj.26.203
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Expression Analysis of a GnRH-Like Dodecapeptide in the Swordtip Squid,Loligo edulis

Abstract: In vertebrates, gonadotropin-releasing hormone (GnRH), which is synthesized in the brain, is a key peptide involved in gonadal maturation regulated by the brain-pituitary-gonadal axis. GnRH isoforms and their primary structures have recently been determined in two species of non-chordates, the octopus (Octopus vulgaris) and sea hare (Aplysia californica), which are mollusks. Octopus and sea hare GnRHs are dodecapeptides that contain the structural core of chordate GnRH; however, chordate GnRHs, including tunic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…A partial cDNA characterized by an exactly similar sequence to the oct-GnRH precursor has been cloned from the cuttlefish S. officinalis, and its expression has been detected in the brain and ovary (Di Cristo et al, 2009a). The open reading frame of the cDNA cloned from the central nervous system (CNS) of swordtip squid Uroteuthis edulis, is 80.5% similar to that of oct-GnRH in nucleotide sequence (Onitsuka et al, 2009) (Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%
“…A partial cDNA characterized by an exactly similar sequence to the oct-GnRH precursor has been cloned from the cuttlefish S. officinalis, and its expression has been detected in the brain and ovary (Di Cristo et al, 2009a). The open reading frame of the cDNA cloned from the central nervous system (CNS) of swordtip squid Uroteuthis edulis, is 80.5% similar to that of oct-GnRH in nucleotide sequence (Onitsuka et al, 2009) (Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%
“…), a sea urchin ( Strongylocentrotus purpuratus ), and a leech ( Helobdella robusta ) by searching within the expressed sequence tag database (Tsai and Zhang, 2008; Roch et al, 2011). GnRH from two species of cephalopod mollusk, common cuttlefish ( Sepia officinalis ; Di Cristo et al, 2009) and sword tip squid ( Loligo edulis ; Onitsuka et al, 2009) share the same peptide sequence as the common octopus ( Octopus vulgaris ; Iwakoshi et al, 2002). The isolated or deduced sequences of these GnRH peptides have either 11 or 12 amino acids with the insertion of 2 amino acids downstream of the N-terminal pyroglutamyl residue (Iwakoshi et al, 2002; Zhang et al, 2008; Di Cristo et al, 2009; Onitsuka et al, 2009; Tsai et al, 2010; Roch et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…GnRH from two species of cephalopod mollusk, common cuttlefish ( Sepia officinalis ; Di Cristo et al, 2009) and sword tip squid ( Loligo edulis ; Onitsuka et al, 2009) share the same peptide sequence as the common octopus ( Octopus vulgaris ; Iwakoshi et al, 2002). The isolated or deduced sequences of these GnRH peptides have either 11 or 12 amino acids with the insertion of 2 amino acids downstream of the N-terminal pyroglutamyl residue (Iwakoshi et al, 2002; Zhang et al, 2008; Di Cristo et al, 2009; Onitsuka et al, 2009; Tsai et al, 2010; Roch et al, 2011). The primary structure of these six novel forms of GnRHs differs markedly from that of chordate GnRHs, challenging the conventional belief that the decapeptide structure of chordate GnRHs is universally conserved.…”
Section: Introductionmentioning
confidence: 99%
“…This finding accelerated the study of protostome GnRH, the existence of which had previously been suggested by immunohistochemistry using a heterologous antibody raised against vertebrate GnRH. The full-length cDNA of oct-GnRH was subsequently isolated from the swordtip squid Loligo edulis [8] and the European common cuttlefish Sepia officinalis [9]. The fulllength cDNA of a GnRH-like peptide has also been isolated from the central nervous system (CNS) of a gastropod mollusk, the sea hare Aplysia californica [10].…”
Section: Introductionmentioning
confidence: 99%